Associations between physical activity, long COVID symptom intensity, and perceived health among individuals with long COVID - Sirotiak, Zoe; Lee, Duck-chul; Brellenthin, Angelique G. (Frontiers in Psychology, 2024)
Introduction Physical activity (PA) is associated with better perceived health among individuals with chronic conditions. However, PA’s relationship with perceived health in people with long COVID is unclear and may be modified by long COVID symptom burden. Methods Participants with self-reported long COVID (N = 379) responded to an online survey cross-sectionally assessing PA levels, perceived physical and mental health, and intensity of CDC-defined long COVID symptoms on a 0–100 scale. Linear regression analyses assessed the associations between PA and perceived physical and mental health, after accounting for sociodemographic, health behavior, and long COVID intensity variables, with post-hoc analyses comparing health across PA levels. Results Increasing levels of PA were associated with increases in perceived physical health (β = 0.27, p < 0.001) and mental health (β = 0.19, p < 0.001) after accounting for sociodemographic and health behavior variables. PA remained significantly associated with perceived physical health (β = 0.15, p < 0.001) but not perceived mental health (β = 0.09, p = 0.067) after the adding long COVID intensity to the model. Insufficiently active and active groups reported significant better physical and mental health than the inactive group (ps < 0.05), while the highly active group did not significantly differ from any other group on perceived physical or mental health (ps > 0.05). Inactive individuals reported significantly greater long COVID symptom burden compared to each other PA level (ps < 0.05). Conclusion Higher levels of PA may be associated with better physical health among individuals with long COVID, even after accounting for symptom intensity. However, long COVID symptom intensity may confound the relationship between PA and mental health among individuals with long COVID.